Da Rio+20 a Rio-2016:: caminhos da sustentabilidade nas olimpíadas - Flores, Maureen; Puppim de Oliveira, José A. (Sustainability in Debate, 2013)
This article seeks to analyze the way the Olympic Games have incorporated the main sustainability commitments agreed upon during the Rio 92, Rio + 10 and Rio + 20 Conferences, both in their planning and their operational processes, thus influencing host cities in the construction of the Games’ legacy. Tourism is one of the mainstays of Rio’s economy, and the link between the Games and the city’s images will be lasting. The Olympic games will influence the quantity and the quality of the touristic demand during, but especially after the event. They will showcase the city’s innovative initiatives for sustainability. The IOC can play a vital role orienting those initiatives. The Games’sustainability legacy may constitute an opportunity for the city to change its image for ever. We still have three years ahead of us to advance, but the basis need to be settled now.